Legal Analysis of Crimes Committed Through Shell Companies and The Role of Prosecutors in Combating Such Crimes - Hutabarat, Dwi Natalia Martama; Manullang, Herlina (Golden Ratio of Data in Summary, 2025)
This paper aims to analyze the legal aspects related to crimes or violations committed by forming shell companies and the role of prosecutors in taking action against crimes committed through shell companies that have the potential to harm the State. Shell companies are often used as a tool to hide assets and commit various illegal acts such as tax evasion, money laundering and manipulation of financial statements. The existence of shell companies is a challenge for law enforcement agencies, especially for prosecutors, who play an important role in the investigation and prosecution process. Using the normative research method, this research analyzes the applicable laws and regulations, especially in Indonesia, and the steps taken by prosecutors in taking action against crimes or violations of the law committed through shell companies. The results of this study show that there is a legal vacuum in the supervision and prosecution of shell companies, which often operate across state jurisdictions, making investigation and prosecution difficult. The role of prosecutors is important to conduct in-depth investigations, collect evidence, and cooperate with other institutions to recover state losses. Therefore, stricter regulations and increased inter-agency coordination are needed to strengthen the role of prosecutors in combating shell company crime.